Varieties of familialism: Comparing four southern European and East Asian welfare regimes - Chiara Saraceno (Journal of european social policy, 2016)
The aim of this article is to articulate the concepts of familialism and defamilialization as well as their indicators to assess whether and how welfare states, or regimes, differ not only in the degree to which they are defamilialized but also in the specific familialism form. In other words, it assesses whether family responsibility in a given area (and its gender dimension) is only assumed without public policy support or, on the contrary, whether it is actively enforced by laws or supported by income transfers and time allocation. The same diversification also exists for the opposite concept, defamilialization, which may happen through positive, direct or indirect policy interventions or because of the lack of such interventions, encouraging recourse to the market. The article shows that when considering these distinctions in the analyses, the profiles of countries that are usually generically described as `familialistic welfare states', such as Italy and Spain in Europe or Japan and Korea in East Asia, and their similarities and differences partly differ from those that emerge when considering only a simplified familialism – defamilialization dichotomy, in so far both familialism and defamilialization may occur, and be combined, through distinct means, offering, therefore, also different options.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich. / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; Defamilialization; familialism; South East Asia; Southern Europe; welfare regimes